Microbiome-Induced Microenvironmental Changes Before and After Breast Cancer Treatment - Jeongshin An; Hyungju Kwon; Young Ju Kim; Byung-In Moon (Microorganisms)
Breast cancer treatment, including surgery, chemotherapy, radiotherapy, and endocrine therapy, can affect the microbiome and microenvironment of the human body. The present study examined how the microbiome changes before and after treatment in patients with breast cancer and explored variations in the expression of putative proteins linked to these shifts. Forty-five patients enrolled in this study, and blood samples were collected and sequenced to analyze microbiome composition. Using these sequences, we estimated and compared the putative protein expression levels. In addition, complete blood count results were analyzed to evaluate treatment-induced alterations. The findings indicate that treatment leads to microbiome modifications associated with changes in the human microenvironment. Moreover, key putative proteins involved in these processes were identified. This study provides valuable insights into how breast cancer treatment affects the microbiome and helps elucidate the potential role of microbial protein expression in patient outcomes.